A genome‐wide association study indicates LCORL/NCAPG as a candidate locus for withers height in German Warmblood horses. (18th February 2013) - Tetens, J.; Widmann, P.; Kühn, C.; Thaller, G.
Summary A genome‐wide association scan for loci affecting withers height was conducted in 782 German Warmblood stallions, which were genotyped using the Illumina EquineSNP50 Bead Chip. A principal components approach was applied to correct for population structure. The analysis revealed a single major QTL on ECA3 explaining ~18 per cent of the phenotypic variance, which is in concordance with recent reports from other horse populations. The LCORL/NCAPG locus represents a strong candidate gene for this QTL. This locus is among a small number that have consistently been identified to influence human height in several large meta‐analyses. Furthermore, a mutation within the NCAPG gene was found to affect growth and body frame size in cattle. Together with the results of this study in German Warmbloods, these findings strongly indicate LCORL/NCAPG as a candidate locus for withers height in horses. Further studies are, however, needed to confirm this.